Crime and Criminal Justice in Modern Germany - Wetzell, Richard F. (Studies in German History, 2014)
The history of criminal justice in modern Germany has become a vibrant field of research, as demonstrated in this volume. Following an introductory survey, the twelve chapters examine major topics in the history of crime and criminal justice from Imperial Germany, through the Weimar and Nazi eras, to the early postwar years. These topics include case studies of criminal trials, the development of juvenile justice, and the efforts to reform the penal code, criminal procedure, and the prison system. The collection also reveals that the history of criminal justice has much to contribute to other areas of historical inquiry: it explores the changing relationship of criminal justice to psychiatry and social welfare, analyzes representations of crime and criminal justice in the media and literature, and uses the lens of criminal justice to illuminate German social history, gender history, and the history of sexuality.